2018
DOI: 10.1111/pbr.12608
|View full text |Cite
|
Sign up to set email alerts
|

Breeding for boron tolerance in lentil (Lens culinaris Medik.) using a high‐throughput phenotypic assay and molecular markers

Abstract: This study describes the identification of a quantitative trait locus (QTL) in the recombinant inbred line population of ILL2024 × ILL6788 and subsequent validation of associated molecular markers. A high‐quality genetic linkage map was constructed with 758 markers that cover 1,057 cM, with an average intermarker distance of 2 cM. QTL analysis revealed a single genomic region on Lc2 to be associated with B tolerance and accounted for up to 76% of phenotypic variation (Vp). The best markers for B tolerance were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…BOR toxicity tolerance was assessed using a hydroponic screening method as described in ( Rodda et al., 2018 )), where six plants per genotype were grown in trays of peat plugs floating in a dilute boric acid solution for two weeks. Lentil varieties previously characterized as intolerant (PBA Blitz and Cassab) and tolerant (ILL2024) were used as internal controls to determine the ideal assessment time.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…BOR toxicity tolerance was assessed using a hydroponic screening method as described in ( Rodda et al., 2018 )), where six plants per genotype were grown in trays of peat plugs floating in a dilute boric acid solution for two weeks. Lentil varieties previously characterized as intolerant (PBA Blitz and Cassab) and tolerant (ILL2024) were used as internal controls to determine the ideal assessment time.…”
Section: Methodsmentioning
confidence: 99%
“…These variations arise primarily from the influence of various biotic and environmental stress factors. Of these, ascochyta blight, botrytis grey mould, boron and salinity have been identified as key limiting factors across a wide range of production regions ( Davidson et al., 2016 ; Sudheesh et al., 2016 ; Rodda et al., 2017 ; Rodda et al., 2018 ; Dissanayake et al., 2020 ; Kumar et al., 2021 ) that can result in yield losses of 30-40% ( Kumar et al., 2013 ). Climate variability and complex genotype-by-environment (G × E) interactions on the expression of phenotypic traits also contribute to low genetic gain in lentil breeding ( Kumar and Ali, 2006 ; Kumar et al., 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Yamauchi et al [28] identified four SNP rich regions to genotype 21 cultivated hop varieties from Europe and the United States, and Van Holle et al [45] identified 1,830 highly discriminant SNPs to genotype 56 of the most commercially relevant hop cultivars. KASP markers are starting to gain attention as a valuable genetic tool in plants for genotyping and marker assisted selection (MAS) [124][125][126][127][128][129].…”
Section: Identity Verification With the 9-ssr And 25 Kasp Fingerprint...mentioning
confidence: 99%